Laser Application in Periodontics - Seyyedi, Seyyed Amir; Khashabi, Ehsan; Falaki, Farnaz (Journal of Lasers in Medical Sciences, 2012)
INTRODUCTION: The use of lasers for treatment has become a common phenomenon in the medical field. Currently, numerous laser systems are available for dental use. The use of lasers for periodontal treatment becomes more complicated because the periodontium consists of both hard and soft tissues. METHODS: Related articles were gathered and selected carefully and reviewed. Among the many lasers available, high power lasers such as Carbon Dioxide Laser (CO2),Neodymium-Doped Yttrium Aluminium Garnet (Nd:YAG) and diode lasers can be used in periodontics. The use of these lasers is limited to gingivectomy, frenectomy and similar soft tissue procedures including the removal of melanin pigmentation of gingiva. Recently, Erbium: Yttrium Aluminium Garnet(Er:YAG) and Erbium, Chromium doped Yttrium Scandium Gallium Garnet (Er,Cr:YSGG) lasers are used for scaling, root debridement, cutting, shaving, contouring and resection of oral osseous tissues. RESULTS: In addition to their surgical applications, low-level lasers such as Er:YAG laser irradiation promotes osteoblast proliferation showing higher and favorable bone tissue regeneration. These findings suggest faster bone tissue healing following periodontal and peri-implant low level laser therapy. CONCLUSION: Advantages of laser treatment in periodontics are effective and efficient soft and hard tissue ablation with a greater hemostasis, bactericidal effect, minimal wound contraction, faster bone tissue healing, minimal collateral damages along with reduced use of local analgesia.